AKIBAT HUKUM PENDAFTARAN HAK TANGGUNGAN ATAS SERTIPIKAT YANG OBJEK DAN SUBJEKNYA SATU NAMUN KEMUDIAN DIKETAHUI SERTIPIKATNYA GANDA - JULI ASTUTI (PREMISE LAW JURNAL, 2015)
The ownership certificate, issued by the Land Office in Pidie District in 2001, was made as collateral and the hypothecation was registered on more time in 2008. By the time the Head of the Section in the Hypothecation and Land Registration by 2012, the archives were organized and some of them were burned up, using descriptive analytic method. The cause of the change of the certificate was the owner’s bad faith and the negligence of the Land personnel in examining the dossiers in issuing the new certificate. Legal consequence of hypothecation on the certificate which has one object and subject is that there is no security of the collateral given by debtor to creditor. The legal solution of this case can be done through criminal and civil hearings, mediated by the Land Office. Keywords: Registration of Hypothecation, Double Certificate